Prognostic value of different levels of uric acid in patients with coronary chronic total occlusion undergoing percutaneous coronary intervention - Ayoub, Mohamed; Mashayekhi, Kambis; Behnes, Michael; Schupp, Tobias; Akın, Muharrem; Forner, Jan; Akın, Ibrahim; Neumann, Franz-Josef; Westermann, Dirk; Rudolph, Volker; Toma, Aurel (Journal of Clinical Medicine, 2023)
Recent data suggest that uric acid (UA) might be an independent predictor of clinical outcomes following percutaneous coronary intervention (PCI). The predictive value of uric acid in patients undergoing PCI for chronic total occlusions (CTO) is unknown. We included patients with CTO who underwent PCI at our center in 2005 and 2012, with available uric acid levels before angiography. Subjects were divided into groups according to uric acid tertiles (<5.5 mg/dL, 5.6-6.9 mg/dL, and >7.0 mg/dL), and outcomes were compared among the groups. Out of the 1963 patients (mean age 65.2 ± 11 years), 34.7% (n = 682) had uric acid concentrations in the first tertile, 34.3% (n = 673) in the second tertile, and 31% (n = 608) in the third tertile. Median follow-up was 3.0 years. Uric acid levels in the first tertile were associated with significantly lower all-cause mortality, as compared to the third tertile, with an adjusted hazard ratio (HR) of 0.67 (95% confidence interval (CI): 0.49 to 0.92; p = 0.012). No significant differences regarding all-cause mortality were found between patients in the first and second tertiles (HR: 0.96 [95% CI: 0.71 to 1.3; p = 0.78]). High levels of uric acid emerged as an independent predictor of all-cause mortality in patients with chronic total occlusion treated with PCI. Hence, uric acid levels should be incorporated into the risk assessment of patients with CTO.